Signal Characteristics of Land Mobile Satellites in Urban and Suburban Equatorial Regions: A Study of S/N Ratios in Fixed and Mobile Conditions - Hasanuddin, Zulfajri Basri; Fujisaki, Kiyotaka; Sampebatu, Limbran (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The increasing demand for mobile communication services in Indonesia underscores the necessity for reliable satellite mapping systems, particularly in equatorial regions where empirical data is scarce. This study aims to fill this research gap by evaluating the signal strength and quality for land mobile satellites in Pare-Pare City and Sidrap Regency. Utilizing a cost-effective laptop-based system alongside a handheld GPS receiver, we conducted measurements under both fixed and mobile conditions at various locations. Our analysis, performed using Matlab R2023b, identified notable variations in Signal-to-Noise Ratio (SNR), primarily ranging from 20 to 49 dBHz, with peak values of around 50 dBHz recorded in suburban areas. These findings indicate that local obstructions significantly affect GPS accuracy. The implications of this research are twofold: theoretically, it enriches the existing literature on GPS performance in equatorial environments, and practically, it offers actionable insights for optimizing satellite deployments to enhance communication reliability. By providing essential empirical evidence, this study represents a valuable contribution to the understanding of satellite communication dynamics in Indonesia, paving the way for more effective navigation and communication solutions in challenging equatorial settings.